Zjawisko pozoru w systemie kształcenia uczniów niepełnosprawnych – próba identyfikacji i propozycje rozwiązań - Parys, Katarzyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
The article points out the phenomenon of pretence in education of students with disabilities. Activities, which are assumed to help equalization of educational opportunities for students with disabilities – but in effect that is not achieved, were discussed. The author indicates possible causes of selected sham activities and she suggests solutions that can help reduce the pretence in the field of special education.